Transient osteoporosis of the hip associated with pregnancy: case report - Terzi, Rabia; Özer, Tülay; Terzi, Hasan; Kale, Ahmet (International Journal of Research in Medical Sciences, 2017)
Transient osteoporosis of the hip associated with pregnancy is a clinical condition with an unclear etiology seen in pregnant women in the 3rd trimester that may lead to severe pain and disability. In this article we present a case getting transient osteoporosis associated with pregnancy based on clinical and radiological findings and discussed it under the guidance of the literature.